Linkpreserving interferenceminimisation channel assignment in multiradio wireless mesh networks. (2015) - Yen, LiHsing; Huang, KuoWei
Using multiple channels with multiple radios per node in a wireless mesh network can potentially improve system capacity. This design requires the appropriate assignments of channels/radios to wireless backhaul links and creates a tradeoff between conflicting constraints and requirements. This study attempts to maximise the number of operative links, where a link is operative if radios at both ends of the link share a common channel (i.e., are linkpreserving) and experience sufficiently low cochannel interference. These two criteria are conflicting in nature. A linkcentric, channelfirst radio resource assignment scheme that considers physical interference model and tight radio constraint is proposed. The proposed approach ensures link preservation and assigns channels to links based on the predicted upper bound and lower bound of the accumulated cochannel interference associated with particular assignments. Simulation results indicate that the proposed algorithm outperforms existing approaches in the number of operative links, particularly when only a few channels, or many radios, are available.